Fuzzy Logic Controller Application for Automatic Charging System Design of a Solar Powered Mobile Manipulator - Fradina Septiarini; Tresna Dewi; Rusdianasari Rusdianasari (Universitas Sriwijaya, 2021)
Agriculture is a vital industry that affects the livelihoods of many people. Given the reduction in agricultural employees and the increasing strain on farmers, this sector requires convenience, which the automation system may provide. One of the automations is mobile manipulator implementation to substitute farmers. This study investigates the automatic battery charging system supported by the Fuzzy Logic Controller (FLC) to power a mobile manipulator. The application of solar charging is an ideal power source for the robot applied in the open field with high irradiance all year long. This charging system is equipped with IoT monitoring online to monitor the available power produced by solar panel and the battery capacity condition. The effectiveness of the proposed method is proven by experiments conducted for ten times charging in ten days, where the highest power produced by the panel is 1.080 W with 0.563 W charged to the battery. The highest irradiance comes with the highest surface panel temperature of 58.9OC at the irradiance rate of 1021 W/m2. The experimental results show the possibility of the solar-powered robot, which is ideal for agriculture implementation.